Stabilisasi Tanah Lempung Desa Mentoro Kecamatan Soko Kabupaten Tuban dengan Variasi Limbah Bata Merah dan Serbuk Kapur Rengel Tuban - Zakina, Bella Lutfiani Al; Saputri, Lailia Rohmatun; Zainuddin, Zainuddin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Soil is an important element in a road construction, where the soil is a support for the structure above it. However, the conditions found in the field are found in many soils whose physical properties do not meet the standards for compressibility, permeability, and plasticity. The aim of the study was to determine the CBR value of clay soil after it was mixed with a mixture of red brick powder and Rengel lime powder. This research method is experimental research (true experiment). The results of this study obtained that soil with a mixture of 9% lime + 9% red brick produced a CBR value of 66.36% of the original soil CBR value of 17.22%. The CBR value achieves optimum stability in the soil composition with a mixture of 9% lime + 9% red brick resulting in a CBR value of 66.36%.